Peran Whistleblowing dalam Pencegahan Fraud Pengelolaan Dana Desa di Provinsi Jambi - Ratih Kusumastuti; Iskandar Sam; Derist Touriano (JAKU (Jurnal Akuntansi & Keuangan Unja) (E-Journal), 2023)
The purpose of this study is to describe and provide empirical evidence regarding the role of whistleblowing in preventing fraud in the management of Village Funds. This research is a quantitative descriptive study. Source of data used in this research is primary data. Data collection was carried out using a survey method in the form of a questionnaire. The population in this study are villages that receive Village Funds spread across 9 districts in Jambi Province. The sample used in this study used a purposive sampling technique in 18 villages spread over 9 regencies in Jambi Province. data analysis using Structural Equation Modeling (SEM). The results of the study prove that Whistleblowing has a significant positive effect on Fraud Prevention. Then, Financial Reporting Compliance has a positive effect on Fraud Prevention. The results of the Moderation Test prove that Morality is not a moderating variable for the whistleblowing relationship with Fraud Prevention.